Сущность рекреационного потенциала - Туголукова, Е.Ю. (Культура народов Причерноморья, 2014)
В статье на основании изучения и анализа существующих точек зрения раскрыта
сущность понятия «рекреационный потенциал». Изучены составляющие целостного представления о
самом понятии рекреация, рекреационном потенциале, рекреационные ресурсы. Проанализированы
существующие научные точки зрения к данной терминологии. Анализируется структура
рекреационного потенциала. Разработаны и предложены собственные значения определений. У статті на підставі аналізу існуючих точок зору розкрито сутність поняття
«рекреаційний потенціал». Вивчені складові цілісного уявлення про саме поняття рекреація,
рекреаційному потенціалі, рекреаційні ресурси. Проаналізовано існуючі наукові точки зору до даної
термінології. Аналізується структура рекреаційного потенціалу. Розроблено та запропоновано власні
значення термінів. The article based on an analysis of existing points of view reveals the essence of the concept of
"recreational potential." Studied components of a holistic view of recreational potential. We analyze the
structure of the recreational potential. The term "recreational potential" is not completely certain of diversity
and complexity of the system, and therefore requires further study. Recreation refers to the type of activity that
have a strong resource dependency, showing the similarities in the forest industry with mining, fishing and
agriculture. There is no single definition of "recreation" in different countries differ significantly its concepts, as
well as the very notion of a very capacious and implies a tourism, recreation, sightseeing, free time and leisure.
Therefore, an important part of the recreational potential of recreational resources. Recreational potential can
be determined by the characteristics of "recreational resources", which has a particular region or territory.
Thus, in our understanding, recreational potential - a set of identified resources that need to be converted for
their direct use in the provision of recreation services, medical procedures, and direct sales. In turn, under the
recreational resources - all kinds of resources that do not require additional changes and ready to use for
recreation and healing people, including spa treatment and tourism. Recreational resources are treated as a
combination of natural, socio-cultural and socio-economic resources, acting as a condition to meet the
recreational needs of the person.